Strategic Leadership Transformation of Indonesia's Defense in The Era of Non-Traditional Security Threats: A 5-Pillar Conceptual Framework - Hengky Tomuan P. Aritonang; A. Adang Supriyadi (Lembaga Bale Literasi, 2026)
The continuously transforming global security landscape demands a new defense paradigm that transcends conventional military threats. Indonesia, as the world's largest archipelagic state with a crucial geostrategic position, faces a spectrum of non-traditional threats that are asymmetric, transboundary, and multidimensional, encompassing terrorism, cyber threats, maritime security challenges, climate change, and pandemics. This article aims to examine patterns of strategic leadership transformation in Indonesia's defense sector in responding to non-traditional security threats, while proposing an integrated new conceptual framework. Through a systematic literature review of 36 scholarly publications, this research reveals that Indonesia's strategic leadership transformation is moving from conventional hierarchical models toward adaptive leadership, yet faces structural obstacles including inter-institutional coordination gaps, legal ambiguity in Military Operations Other Than War (MOOTW), limited civilian capacity in defense oversight, and institutional resistance to military innovation adoption. As a novelty contribution, this article proposes a New 5-Pillar Conceptual Framework integrating: (1) Adaptive Leadership, (2) Civil-Military Governance, (3) Digital Transformation, (4) Hybrid Defense Doctrine, and (5) Regional Strategic Partnership. This framework is designed to bridge the gap between normative defense policy and operational implementation, while strengthening national resilience in facing an ever-evolving threat landscape.